Status moves: Evaluations and effectiveness of status behaviors. (January 2019) - Kim, Hee Young; Pettit, Nathan C.; Reitman, Laura E.
This paper examines reactions of in-group members and third-party observers to behaviors people perform to affect the status hierarchy of their group (i.e., status moves). We understand status hierarchies to be "negotiated, " where "status moves" are a means to negotiate the group's informal order. Results indicate that the valence (positive vs. negative) and context (initiating vs. reacting) of the status move interactively affect observers' reactions (Studies 1 and 3), and that these reactions are explained by perceptions of the actor's self- versus group concern (Studies 1–2 and 4) in both experimental as well as more naturalistic contexts. Specifically, initiating status moves elicit stronger reactions, with positive/negative initiating moves resulting in recommendations of greater reward/punishment and status gain/loss for the actor (Studies 1 and 3) than reacting moves. Overall, we offer a first systematic examination of status moves and how people perceive and react to them.